A Polish and German Population Study of Quality of Life, Well-Being, and Life Satisfaction in Older Adults During the COVID-19 Pandemic - Bidzan-Bluma, Ilona; Bidzan, Monika; Jurek, Paweł; Bidzan, Leszek; Knietzsch, Jessica; Stueck, Marcus; Bidzan, Mariola (Frontiers in Psychiatry, 2020)
Introduction: Psychological studies undertaken during the COVID-19 pandemic rarely include people in their 60s or older. In our study, we studied the predictors of quality of life, well-being, and life satisfaction (including risky behavior, trait anxiety, feeling of threat, sleep quality, and optimism) during the pandemic in older people from Germany and Poland and compared them to three different age groups. Methods: A total of 494 adults in four groups−60+ (N = 60), 50–60 (N = 139), 36–49 (N = 155), <35 (N = 140)—completed validated self-report questionnaires assessing: socio-demographic data, quality of life, trait anxiety, risk tolerance, Coronavirus threat, optimism regarding the pandemic, difficulty relaxing, life satisfaction, well-being, and sleep quality during the pandemic period. Results: Older people rated their quality of life higher than did young (mean difference=0.74, SE=0.19, p < 0.01) and middle-aged (mean difference=0.79, SE=0.18, p < 0.01) participants, rated their life satisfaction higher than young (mean difference=1.23, SE = 0.31, p < 0.01) and middle-aged (mean difference=0.92, SE = 0.30, p < 0.05) participants, and rated their well-being higher than young (mean difference=1.40, SE = 0.31, p < 0.01) and middle-aged (mean difference=0.91, SE = 0.31, p < 0.05) participants. They also experienced lower levels of trait anxiety and Coronavirus threat (mean difference=-9.19, SE = 1.90, p < 0.01) than the younger age groups. They experienced greater risk tolerance (mean difference=1.38, SE=0.33, p < 0.01), sleep quality (F =1 .25; eta2 = 0.01), and optimism (F = 1.96; eta2 = 0.01), and had less difficulty relaxing during the pandemic (F = 3.75; eta2 = 0.02) than middle-aged respondents. Conclusions: Quality of life, life satisfaction, and well-being during the pandemic is affected by age, trait anxiety, and Coronavirus threat. Older people rated their quality of life, life satisfaction, and well-being during pandemic higher than young people, and experienced lower levels of trait anxiety and Coronavirus threat than the younger age groups. They experienced greater risk tolerance, sleep quality, and optimism, and had less difficulty relaxing than middle-aged respondents.